EFFECT OF HUMIC ACID AND MAXIGROW (ORGANIC FERTILIZER) ON GROWTH, FLOWERING AND YIELD OF SNAKE CUCUMBER (CUCUMIS MELO. L) - Ahmed , Ahmed M. (Science Journal of University of Zakho, 2024)
ABSTRACT: A field trial was implemented at the research center field at general directorate of agriculture, Dohuk Governorate, Iraqi Kurdistan region in summer season of (2022-2023) to find out the impact of foliar application of humic acid at three levels (0, 2, and 4) ml L-1 and Maxigrow (an organic fertilizer) with three levels (0, 1, and 2) ml L-1 and their combinations on outgrowth, flowering and harvest of local snake cucumber. The experiment was organized following a randomized complete block design (RCBD) including three replicates. The data displayed that the individual dose of humic acid at (4) ml.L-1 significantly enhanced foliage traits [number of branches, stem diameter (cm), Leaf area (cm2), plant fresh weight (g), and chlorophyll content (SPAD)] as well as increased flowering characters [number of flowers after 30 days and number of flowers after 40 days] and yielded components [fruit length (cm), fruit diameter (cm), and total yield (ton.ha-1)]. The same profound effect was exhibited by the singular dose of Maxigrow at concentration (2) ml.L-1. However, the highest mean values were produced from humic acid at concentration (4) ml.L-1 in combination with Maxigrow at concentration (2) ml.L-1 in comparison with control. The increased level of humic acid and Maxigrow is advised for organic productivity of local snake cucumber.